OPTIMIZATION STRATEGY OF FUNDING IN SECOND-TIER BANKS - journal, admin; Bakashbayev Azatbek Zharkynbekuly, (Academic Journal of Physical and Chemical Sciences, 2019)
As known, funding is a priority for banking. In pursuit of resources, banks form a funding strategy that provides the highest return on their investments in the relevant assets. This raises the question of what sources of funding to use and what assets to best direct. In the article, the author suggests applying dynamic modeling methods, namely game theory, to optimize the funding strategy of banks. The application of the Brown-Robinson method, the Bayes, Savage, Wald and Hurwitz criteria is used for the task of bank funding optimization.